Effects of Cancer Genetic Panel Testing on at-Risk Individuals. Issue 6 (June 2018) - Frost, Anja S.; Toaff, Miriam; Biagi, Tara; Stark, Elizabeth; McHenry, Allison; Kaltman, Rebecca
Abstract : OBJECTIVE: To evaluate the role of screening patients at increased risk for hereditary cancer syndromes with an extended panel of cancer predisposition genes to identify actionable genetic mutations. METHODS: A retrospective chart review was conducted of all patients presenting to a multidisciplinary cancer program for genetic counseling and testing from January 2015 to December 2016. Individuals presenting to the program were identified as at-risk by a personal or family history of cancer, by their health care provider, or by self-referral. All participants met current National Comprehensive Cancer Network criteria for genetic risk evaluation for hereditary cancer. The results of testing and its implications for management, based on National Comprehensive Cancer Network guidelines, were recorded. RESULTS: Of 670 at-risk patients who underwent genetic testing, 66 (9.9%) had BRCA -limited testing; of these, 26 of 670 (3.9%) had a deleterious or likely pathogenic mutation. Expanded panel testing was done for 560 of the 670 patients (83.4%), and abnormal results were found in 65 of 670 (9.7%); non- BRCA mutations (predominantly CHEK2 ) were found in 49 of the 65 (75%). Abnormal genetic testing was associated with increased surveillance in 96% of those with deleterious mutations, whereas negative testing for a known familial mutation in 45 patients was associated with a downgrade of their risk and reduction of subsequent surveillance and management. CONCLUSION: Guideline-based management is frequently altered by genetic testing, including panel testing, in patients at risk for cancer. We recommend that obstetrics and gynecology providers routinely refer at-risk patients for genetic counseling and testing when clinically appropriate. Abstract : Genetic panel testing is associated with significant management changes in individuals at risk for cancer or cancer syndromes, and obstetrician–gynecologists should prioritize referral of these women within their practice so they can benefit from enhanced genetic evaluation.